USABILITY ANALYSIS OF THE CAREER SYSTEM AT JAMBI UNIVERSITY USING SUS AND HEURISTIC EVALUATION TO IMPROVE EMPLOYER SATISFACTION - Enggrani Fitri, Lucky; Setiawan, Dedy; Kaswari, Teja (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
The Career Information System at Jambi University play a crucial role in providing data on alumni education and career paths. This study evaluates the system’s usability using the System Usability Scale (SUS) and Heuristic Evaluation (HE) to enhance employer and study program satisfaction. This research employs primary data collected from Jambi University alumni through questionnaires. The purposive sampling technique was used, with 50 respondents for the SUS method and 3–5 evaluators for HE. The evaluation results show a SUS score of 63.75, categorized as marginally acceptable with a 65th percentile ranking. The HE assessment yielded a 63% score, indicating that the system is functional but requires improvement. Additionally, the Net Promoter Score (NPS) reflects positive user feedback.This study provides insights for further system development to improve user satisfaction, particularly among employers and study programs at Jambi University.